`int xsin^2x dx` Find the indefinite integral

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To solve the indefinite integral, we follow `int f(x) dx = F(x) +C`

where:

`f(x)` as the integrand function

`F(x)` as the antiderivative of f(x)

`C` as the constant of integration.

For the given integral problem: int x sin^2(x) dx, we may apply integration by parts: `int u *dv = uv - int v *du` .

We may let:

`u = x`  then `du =1 dx` or `dx`

`dv= sin^2(x) dx` then `v = x/2 - sin(2x)/4`

Note: From the table of integrals, we have `int sin^2(ax) dx = x/2 - sin(2ax)/(4a)` . We apply this on `v =int dv =intsin^2(x) dx `  where `a =1` .

Applying the formula for integration by parts, we have:

`int x sin^2(x) dx= x*(x/2 - sin(2x)/4 ) - int (x/2 - sin(2x)/4 ) dx`

                              `=x^2/2 - (xsin(2x))/4 - int (x/2 - sin(2x)/4 ) dx`

For the integral:  `int (x/2 - sin(2x)/4 ) dx` , we may apply the basic integration property: : `int (u-v) dx = int (u) dx - int (v) dx` .

 

`int (x/2 - sin(2x)/4 ) dx =int (x/2) dx -int sin(2x)/4 ) dx`

                                    ` = 1/2 int x dx - 1/4 int sin(2x) dx` .

 

Apply the Power rule for integration:

`int x^n dx = x^(n+1)/(n+1) +c` 

`1/2 int x dx = 1/2*x^(1+1)/(1+1)`

                  `= 1/2* x^2/2`

                  `= x^2/4`

Apply the basic integration formula for sine function: `int sin(u) du = -cos(u) +C` .

Let: `u =2x` then `du = 2 dx` or `(du)/2 = dx` .

`1/4 int sin(2x) dx = 1/4 int sin(u) * (du)/2`

                              `= 1/4 *1/2 int sin(u) du`

                              `= 1/8 (-cos(u))`

                               `= -cos(u)/8`

Plug-in `u = 2x` on `-cos(u)/8` , we get: `1/4 int sin(2x) dx =-cos(2x)/8` .

Combining the results, we get:

`int (x/2 - sin(2x)/4 ) dx =x^2/4 - (-cos(2x)/8) +C`

                                     ` =x^2/4+ cos(2x)/8 +C`

Then, the complete indefinite integral will be:

`int x sin^2(x) dx=x^2/2 - (xsin(2x))/4 - int (x/2 - sin(2x)/4 ) dx`

                               `=x^2/2 - (xsin(2x))/4 -(x^2/4+ cos(2x)/8) +C`

                               `=x^2/2 - (xsin(2x))/4 - x^2/4 - cos(2x)/8 +C`

                               `= (x^2)/4- (xsin(2x))/4- cos(2x)/8 +C` 

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial